CONTRASTIVE STUDY OF ASPECT BETWEEN MUNA AND INDONESIAN LANGUAGES - Haerun Ana (Humaniora, 2014)
This paper, which is a contrastive analysis, is concerned with the study of aspect in Muna and Indonesian languages with aims to describe the similarity and difference of aspect in both languages. It uses both oral and written data which are collected by using recording and introspection techniques, and analyzed by using contrastive analysis. The result of the study shows that Muna uses infix {-um-} and prefix {m-} to express future event, while Indonesian uses lexicon akan ‘will’ or mau ‘want’ as future aspects; Muna uses nando and Indonesian uses sedang, sementara, masih, tengah, baru, and pada before the verb as durative or progressive aspects; Muna uses suffix {mo-} and lexicon padamo to express past event, while Indonesian uses only lexicon sudah or telah as perfective aspects; and Muna differentiates the concept of negative sentences in the past and in the future; Muna uses lexicon miina ‘did not’ to express negative statement in the past, and uses prefix {pa:-} ‘will not’ to express negative statement in the future, while Indonesian does not differentiate positive and negative statement of aspect.